ANTI-MALARIAL EFFECTS OF FIVE TRADITIONAL NIGERIAN MEDICINAL PLANT EXTRACTS ON PLASMODIUM BERGHEI-INFECTED RATS - Igbokwe, Ugochukwu Vincent; Eze, EJIKE DANIEL; Adams, Moses Dele; Rabiu, Karimah Mohammed; Ezekiel, Iliya; Ajeka, Prisca Ojochogu; Okpara, Peace Ogechukwu (FUDMA JOURNAL OF SCIENCES, 2021)
This work focusses on comparative determination of the effects of plant extracts: bitter leaf (BL), sour lime (SL), grape (G), pawpaw (PP) and unripe pineapple (UPA) in female rats induced into malaria with Plasmodium berghei. Thirty female rats weighing 120-160 g were allotted into five groups (n=6). Group A (negative control) were infected but not treated. Animals in Groups B–E which were infected were given 500 mg/kg body weight (BW) of malanter DS (reference antimalarial drug), 500 mg/kg BW of BL, 250 mg/kg BW each of SL and BL as well as 250 mg/kg BW each of G, PP and UPA. Treatment was done orally once daily for 14 days after which a few related analyses were carried out. Before treatment, parasitemia count of animals in groups B-E was substantially (p<0.05) higher when juxtaposed with group A. AST and ALT activities was substantively (p<0.05) elevated in group B-E when matched with group A. Plasmodium berghei induction notably (p<0.05) lowered white blood cell (WBC) and monocyte (Mono) levels at all groups. After 7 days of treatment, the extracts and drug which appreciably (p<0.05) lowered plasmodium count, RBC, WBC, PCV, Hb, Plat, Lymph, Mono, Granul levels did not meaningfully (p>0.05) affect the activities of ALP, AST and ALT. After 14 days of treatment, the extracts and drug exceptionally (p<0.05) reduced plasmodium count, WBC and ALP activity at all groups. These results give suggestive evidence that the plant extracts either singly or combined, could be a promising anti-plasmodial candidate.